Case report: carcinosarcoma of the fallopian tube. (9th November 2022) - Sun, Y; Takeda, K; Stalls, J; Sutton, A; Chen, S
Abstract: Introduction/Objective: Carcinosarcoma is a malignant biphasic tumor composed of carcinomatous and sarcomatous elements. Carcinosarcoma of the fallopian tube is an extremely rare malignancy with fewer than 100 cases reported in the literature. We report a rare case of carcinosarcoma arising from the right fallopian tube. Methods/Case Report: A 72-year-old female presented with worsening vaginal discharge and abdominal cramps. Abdominal computed tomography detected a right adnexal mass. A torsed fallopian tube with a large mass was identified intraoperatively. Grossly, a 3.1 cm tan friable mass was seen protruding from the right fallopian tube lumen with numerous detached tumor fragments (9.4 cm in aggregate). Microscopically, the tumor was biphasic with a major mesenchymal component and minor epithelial component. A solid pattern of spindled and epithelioid cells with heterologous element of chondrosarcoma and a separate component with features of high-grade serous carcinoma in cribriform and solid sheets with slit-like spaces were seen. Both components showed marked nuclear atypia, pleomorphism, prominent nucleoli, and frequent mitoses. Both components were positive for p53, PAX-8, and beta- catenin immunohistochemistry, with a Ki-67 index of 80-90%. The sarcoma component was positive for p16, vimentin, and smooth muscle actin; the carcinoma component was positive for WT1, pan-cytokeratin, and cytokeratin 7. Pelvic washings were negative for malignancy. Metastases were not identified. Chemotherapy with paclitaxel and carboplatin was initiated with no recurrence identified 17 months after treatment. Results (if a Case Study enter NA): N/A Conclusion: Proper identification and reporting of rare malignancies, such as this fallopian tube carcinosarcoma, with treatment and follow up, provide oncologists with the necessary information to advance treatment.